Characterization of nickel zinc oxide anode materials synthesized by a hydrothermal method / Nurnazurah Dhabitah Zainal Abidin - Zainal Abidin, Nurnazurah Dhabitah (2019)
NiZn2O4 samples anode materials were prepared by hydrothermal reaction and its physical characterization was being analysed by using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), X-ray diffractometry (XRD), thermogravimetric analysis (TGA) and attenuated total reflection-fourier transform infra-red (ATR-FTIR. The synthesized anode materials morphology was observed by SEM-EDS and the result show the rough surface of sample and irregular shape of sample as well as the composition of element oxygen, sulphur, nickel and zinc as the major elements in NiZn2O4. Sharp diffraction peaks obtained in XRD indicate good crystallinity of the sample. The TGA shows the starting loss was discovered as water that contains in the sample turn the percentage decrease. Also, the endothermic and exothermic effect was determined at the second phase and late phase of TGA. The FTIR spectra of NiZn2O4 samples are in the range 1712.97 cm-1 to 535.42 cm-1. The ν(C–O) of ligand is observed at 1260.05 cm-1. The strong band with a shoulder noticed at 1712.97 cm-1 can be attributed to ν(C=O) of the lactone carbonyl group. In this study, the hydrothermal conditions such as alkaline concentration, reaction temperature and duration time have an important influence on the product structure and the performance of the electrode prepared with sample